Architecting Growth in the Digital Era : How to Exploit Enterprise Architecture to Enable Corporate Acquisitions /: How to Exploit Enterprise Architecture to Enable Corporate Acquisitions. (2020) - Henningsson, Stefan; Toppenberg, Gustav Normark
No abstract available